Revitalisasi bahasa Indonesia dalam konteks kebahasaan - Ni Wayan Sartini (Masyarakat, Kebudayaan dan Politik, 2014)
Bahasa Indonesia today faces many misuse in its daily usage. The language disorder appears on many aspects on language usage, such as excessive and misguided use of foreign languages, violation of the rules of Bahasa Indonesia in media and in public places, the inclusion of regional language structure, use of acronyms arbitrarily, the emergence of slank language and so on. Regarding the language disorder, there is a strong need of revitalization of Bahasa Indonesia in linguistic context. Revitalization means re-positioning Indonesian on its right place and return its existing language rules. Revitalization of Indonesian is expected to overcome language misuse, expected to reduce the chaos or even eliminate them. Using Bahasa Indonesia correctly and appropriately means modelling the right stance to the only official language in this country.